Pyogenic Liver Abscess Risk in Patients With Newly Diagnosed Type 2 Diabetes Mellitus: A Nationwide, Population-Based Cohort Study - Wang, Tzu-Yuan; Lai, Hsueh-Chou; Chen, Hsin-Hung; Wang, Mei-Lin; Hsieh, Ming-Chia; Chang, Chwen-Tzuei; Chen, Rong-Hsing; Ho, Chun-Wei; Hung, Yi-Chin; Tseng, Juei-Yu; Lin, Cheng-Li; Kao, Chia-Hung (Frontiers in Medicine, 2021)
Background: To date, no comprehensive epidemiological study exists on pyogenic liver abscess (PLA) risk in patients with newly diagnosed type 2 diabetes mellitus (T2DM) worldwide. Methods: We conducted a retrospective cohort study by using data from Taiwan National Health Insurance Research Database (NHIRD) to examine the association between newly diagnosed T2DM and PLA. The T2DM cohort included patients newly diagnosed as having T2DM (ICD-9-CM:250) from 2000 to 2009, with follow-up until December 31, 2011. The comparison cohort was then recruited through 1:4 random frequency matching with the T2DM cohort. Finally, the adjusted hazard ratios for PLA were compared between the T2DM and comparison cohorts, which included 44728 patients with T2DM and 178912 patients without DM respectively. Results: In T2DM cohort, 166 patients were diagnosed as having PLA (incidence rate = 5.87 per 10000 person-years) and in comparison cohort, 238 patients were diagnosed as having PLA (incidence rate = 2.06 per 10000 person-years). The T2DM cohort exhibited higher PLA risk than did the comparison cohort (hazard ratio = 2.83, 95% confidence interval = 2.32-3.46). Furthermore, the adjusted hazard ratio for PLA risk in T2DM cohort was the highest in those who were younger, man and with duration of DM less than 2 years. In the T2DM cohort, the most common PLA causative agent was Klebsiella pneumonia(KP). In addition, PLA risk was high in T2DM patients with gallstone and cholecystitis. Compared with comparison cohort, patients with T2DM prescribed acarbose has a lower PLA risk, however glyburide significantly increased PLA risk in T2DM cohort. Conclusion: In patients with newly diagnosed T2DM, PLA risk was high and acarbose might reduce PLA risk.